A Systematic Review of the Photoprotective Potential of Native Edible Plants from Mato Grosso do Sul, Brazil - de Castro , Thiago Luis Aguayo; Pinto , Gleice Americo do Carmo; Cardoso, Claudia Andrea Lima (Orbital: The Electronic Journal of Chemistry, 2022)
The state of Mato Grosso do Sul (Brazil) has a rich biodiversity, with varied biomes and many native species. Simultaneously, the plants in the region have been studied for their chemical and biological potential, including photoprotective properties and applications in phytocosmetics. Edible plants have potential application based on the presence of photoprotective and antioxidant compounds in their chemical composition. In this context, the aim was to review systematically studies on the photoprotective action of native food plants from Mato Grosso do Sul in the Scopus database, delimiting for articles published between 2000 and 2020. Only 4.08% of the species presented articles exploring the photoprotective activity, distributed in 10 articles. The extracts evaluated were varied, with different formulations. 40% of the articles addressed ethanolic extracts, 20% hydroethanolic extracts, and 40% vegetable fixed oil. The lowest sun protection factor reported was for the aqueous extract of the fruit pulp of Hymenaea martian Hayne (SPF 0.66) and the highest was for a formulation using Schinus terebinthifolius Radi extracts added to Lanette cream (SPF 32.40). The native food plants of Mato Grosso do Sul are still little explored regarding their photoprotective action, with a lack of in vivo studies.